The CANBACK trial: a randomised, controlled clinical trial of oral cannabidiol for people presenting to the emergency department with acute low back pain. Issue 8 (12th April 2021) - Bebee, Bronwyn; Taylor, David M; Bourke, Elyssia; Pollack, Kimberley; Foster, Lian; Ching, Michael; Wong, Anselm
Abstract: Objective: To assess the analgesic efficacy and safety of single‐dose oral cannabidiol (CBD) as an adjunct to standard care for patients presenting to an emergency department with acute low back pain. Design: Randomised, double blinded, placebo‐controlled clinical trial. Setting: The tertiary emergency department of Austin Hospital, Melbourne. Participants: Patients who presented with acute, non‐traumatic low back pain between 21 May 2018 and 13 June 2019. Intervention: One hundred eligible patients were randomised to receiving 400 mg CBD or placebo in addition to standard emergency department analgesic medication. Main outcome measures: Pain score two hours after administration of study agent, on a verbal numerical pain scale (range, 0‒10). Secondary outcomes were length of stay, need for rescue analgesia, and adverse events. Results: The median age of the 100 participants was 47 years (IQR, 34‒60 years); 44 were women. Mean pain scores at two hours were similar for the CBD (6.2 points; 95% CI, 5.5–6.9 points) and placebo groups (5.8 points; 95% CI, 5.1–6.6 points; absolute difference, –0.3 points; 95% CI, –1.3 to 0.6 points). The median length of stay was 9.0 hours (IQR, 7.4‒12 hours) for the CBD group and 8.5 hours (IQR, 6.5‒21 hours) for the placebo group. Oxycodone use during the four hours preceding and the four hours after receiving CBD or placebo was similar for the two groups, as were reported side effects. Conclusion: CBD was not superior to placebo as an adjunct medication for relieving acute non‐traumatic low back pain in the emergency department. Trial registration: Australian New Zealand Clinical Trials Registry, ACTRN12618000487213 (prospective).